Captioning and Subtitling: Undervalued Language Learning Strategies - Danan, Martine (Meta, 2004)
AbstractAudiovisual material enhanced with captions or interlingual subtitles is a particularly powerful pedagogical tool which can help improve the listening comprehension skills of second-language learners. Captioning facilitates language learning by helping students visualize what they hear, especially if the input is not too far beyond their linguistic ability. Subtitling can also increase language comprehension and leads to additional cognitive benefits, such as greater depth of processing. However, learners often need to be trained to develop active viewing strategies for an efficient use of captioned and subtitled material. Multimedia can offer an even wider range of strategies to learners, who can control access to either captions or subtitles.